2004
DOI: 10.1073/pnas.0307969100
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis double-stranded RNA-binding protein HYL1 plays a role in microRNA-mediated gene regulation

Abstract: The Arabidopsis HYL1 gene encodes a nuclear double-stranded RNA-binding protein. A knockout mutation of the hyl1 gene is recessive and pleiotropic, causing developmental abnormalities, increasing sensitivity to abscisic acid, and reducing sensitivity to auxin and cytokinin. We report that levels of several microRNAs (miRNAs; miR159, -167, and -171) are reduced in homozygous mutant plants, and levels of two of three tested target mRNAs are elevated. Conversely, the miRNA levels are elevated in plants expressing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
393
0
8

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 479 publications
(420 citation statements)
references
References 54 publications
19
393
0
8
Order By: Relevance
“…However, evidences have demonstrated that plant pre-miRNA formation is mediated by the Dicerlike protein 1 (DCL1) (Park et al, 2002;Reinhart et al, 2002;Papp et al, 2003;Kurihara and Watanabe, 2004). With the helps of other factors, such as HYL1 (a two dsRBD-containing nuclear protein) (Han et al, 2004b;Vazquez et al, 2004) and HEN1 (a protein with a dsRBD and a methyltransferase domain) (Boutet et al, 2003;Park et al, 2005;Yu et al, 2005), DCL1 further cleaves a pre-miRNA to a miRNA:miRNA* duplex in nucleus instead of in cytoplasm which usually happen in animal miRNA biogenesis (Park et al, 2002;Reinhart et al, 2002;Papp et al, 2003;Kurihara and Watanabe, 2004). Recent study shows that it is a crucial step in plant miRNA biogenesis to methylate miRNA:miRNA* duplex at the 2 0 hydroxyl groups on the 3 0 most nucleotides (Yu et al, 2005).…”
Section: Microrna Biogenesismentioning
confidence: 99%
“…However, evidences have demonstrated that plant pre-miRNA formation is mediated by the Dicerlike protein 1 (DCL1) (Park et al, 2002;Reinhart et al, 2002;Papp et al, 2003;Kurihara and Watanabe, 2004). With the helps of other factors, such as HYL1 (a two dsRBD-containing nuclear protein) (Han et al, 2004b;Vazquez et al, 2004) and HEN1 (a protein with a dsRBD and a methyltransferase domain) (Boutet et al, 2003;Park et al, 2005;Yu et al, 2005), DCL1 further cleaves a pre-miRNA to a miRNA:miRNA* duplex in nucleus instead of in cytoplasm which usually happen in animal miRNA biogenesis (Park et al, 2002;Reinhart et al, 2002;Papp et al, 2003;Kurihara and Watanabe, 2004). Recent study shows that it is a crucial step in plant miRNA biogenesis to methylate miRNA:miRNA* duplex at the 2 0 hydroxyl groups on the 3 0 most nucleotides (Yu et al, 2005).…”
Section: Microrna Biogenesismentioning
confidence: 99%
“…It was demonstrated that SE also functions in miRNA processing through interacting with HYL1, which acts solely in miRNA biogenesis (Lu and Fedoroff 2000;Han et al 2004;Vazquez et al 2004;Grigg et al 2005;Lobbes et al 2006;Yang et al 2006;Fang and Spector 2007;Dong et al 2008;Laubinger et al 2008). Although there is no evidence that the THO complex plays a direct role in miRNA processing in metazoa, the observed genetic interaction between emu and se-1 prompted us to further examine a potential role for EMU in miRNA biogenesis.…”
Section: Genetic Interactions Between Emu and Mirna Mutantsmentioning
confidence: 99%
“…The second processing step of the Arabidopsis miRNA biogenesis pathway is also catalyzed by DCL1 in nuclear-localized D-bodies, however, DCL1 only requires the assistance of DRB1 to accurately direct this dicing event. 14,15 Following methylation of the 3' 2-nt overhang of each duplex strand by the sRNA-specific methyltransferase HUA ENHANCER1 (HEN1), 9,16 DRB1 orientates the duplex for miRNA* passenger strand degradation. 17 Following nuclear export, a process which for many plant miRNAs requires the assistance of HASTY (HST), 18 the miRNA guide strand is loaded to the RNA-induced silencing complex (RISC).…”
Section: Alternate Approaches To Repress Endogenous Microrna Activitymentioning
confidence: 99%